Sociality and Person-Oriented Approach of Modern Education - Mavrina, Irina A.; Mavrin, Sergey A.; Pruess, Franz; Revyakina, Valentina I.; Semina, Olga A.; Lipatova, Svetlana N.; Kholina, Lyudmila A.; Temerbekova, Alina A. (International Review of Management and Marketing, 2016)
The urgency of the specified problem is determined by the relevance of vocational education at different levels: personal (subject level), social (society level), state (national level). Therefore, the problem of sociality and person-oriented education as a social phenomenon in the Russian Federation requires further investigation in a new social and economic realty. The purpose of this article is to develop structural features of the scientific concept “sociality” and their interrelationship with person-centered education based on the identification of internal contradictions (self-contradictions). The leading method used to research the above mentioned problem is the categorical row method. The essence of this method is in the determination of the basic category in the process of pedagogical analysis, which possesses an internal contradiction – the core of the row and then other categories related to this basic category are determined. These categories are elements or row categories acting on the pendulum principle. Structural features of the scientific concept (category) “sociality” are different bases of social demand formation for education, determined by the person’s needs to get education and needs of society in literate and well-educated professionals working in different fields of human activity, as well as educational levels of various social groups. Practical significance of the findings of investigation concerning the interrelationship between sociality and person-oriented education is in identifying internal contradictions (self-contradictions) specifying the degree of person’s need to consume educational services and render those services in individual and social forms. Keywords: Education, Sociality, Person-Centered Education, Social Demand for Education. JEL Classifications: A23, I23, I26